Multi-functional invisibility cloak for diffusion fields - Goh, Hong Hui (2017)
In this thesis, the Multi-Functional Invisibility Cloak for Diffusion Fields was discussed. The used of the same geometrical symmetry design for thermal diffusion invisibility cloak on the fluid diffusion invisibility cloak was determined which then concludes the final design of the Multi-Functional Invisibility Cloak for Diffusion Fields. Experiment was conducted in assumption of Stokes flow with Reynold’s number « 1 but not approaching zero. However, the design and parameters used for conducting the experiment is optimum enough to conclude the findings.